Jet properties in PbPb and pp collisions at √sNN=5.02 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Nature, 2018)
Modifications of the properties of jets in PbPb collisions, relative to those in pp collisions, are studied at a nucleon-nucleon center-of-mass energy of √ sNN = 5.02 TeV via correlations of charged particles with the jet axis in relative pseudorapidity (∆η), relative azimuth (∆φ), and relative angular distance from the jet axis ∆r = p (∆η) 2 + (∆φ) 2. This analysis uses data collected with the CMS detector at the LHC, corresponding to integrated luminosities of 404 µb −1 and 27.4 pb−1 for PbPb and pp collisions, respectively. Charged particle number densities, jet fragmentation functions, and jet shapes are presented as a function of PbPb collision centrality and charged-particle track transverse momentum, providing a differential description of jet modifications due to interactions with the quarkgluon plasma.